Chronic disease management in general practice: results from a national study. - DARKER, CATHERINE (My University, 2012)
The aim of this study was to provide baseline data on chronic disease management (CDM) provision in Irish general practice (GP). The survey instrument was previously used in a study of primary care physicians in 11 countries, thus allowing international comparisons. The response rate was 72% (380/527).The majority of GPs (240/380; 63%) reported significant changes are needed in our health care system to make CDM work better. Small numbers of routine clinical audits are being performed (95/380; 25%). Irish GPs use evidence based guidelines for treatment of diabetes (267/380; 71%), asthma / COPD (279/380; 74%) and hypertension (297/380; 79%), to the same extent as international counterparts. Barriers to delivering chronic care include increased workload (379/380; 99%), lack of appropriate funding (286/380; 76%), with GPs interested in targeted payments (244/380; 68%). This study provides baseline data to assess future changes in CDM.
PUBLISHED
Keywords: Ageing; Immunology, Inflammation & Infection